PENGARUH KUALITAS LAYANAN DAN PENANGANAN KELUHAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK UMUM SYARIAH DI SURABAYA - Anindhyta Budiarti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
In the service industry is not only a problem in the quality of service only, other issues that need to be considered is how the handling of complaints from users. Of the complaints handling problems can be used as a measure of quality products and services offered. Thus expected to create satisfaction as well as create user loyalty. Similarly, in the banking business after the economic crisis that occurred in 1997. Banking business demanded proactive to enhance service quality and also in the handling of complaints to the customer who is expected to increase customer satisfactionand loyalty. The purpose of this study is Proving and analyze (1) the influence of service quality on customer satisfaction, (2) the influence of the handling of complaints against customer satisfaction, (3) the influence of customer satisfaction on customer loyalty, (4) the influence of service quality on customer loyalty and (5) influence the handling of complaints against customer loyalty Islamic banks in Surabaya. This research was conducted on Islamic banks in Surabaya. This type of research used in this research is the kind of explanatory research. Respondents in this study are customers of Islamic banks in Surabaya. The number of respondents who researched as much as 150 respondents. The analytical tool used in this study is structural equation modeling (SEM). The analysis showed that service quality has a significant influence on satisfaction. Handling complaints have a significant impact on customer satisfaction. Satisfaction has a significant influence on customer loyalty. Service quality has a significant effect on loyalty. Handling complaints have a significant impact on customer loyalty. Customer satisfaction can be improved by improving the quality of service and complaint handling.